Bacterial diversity in the feces of dogs with CPV infection. (August 2018) - Zheng, Yun; Hao, Xiangqi; Lin, Xi; Zheng, Qingxu; Zhang, Wenyan; Zhou, Pei; Li, Shoujun
Abstract: Canine parvovirus (CPV) is a contagious disease in dogs that has high morbidity and mortality. In cases of infection, the pups tend to have a higher mortality and more severe clinical symptoms than the adult dogs because the dehydration is difficult for pups to bear. Following the natural infection, there is a rapid antibody response neutralizing the extracellular virus. As a result, virus titers in tissue and feces become markedly reduced. Hence, it is important to have an effective symptomatic therapy of supporting animals to survive in the early stages of CPV infection. Furthermore, the co-infection with bacteria could increase the severity of lesions and clinical signs as well. In this paper, we obtained the bacterial diversity in feces of CPV infected dogs with the enrichment of five bacteria genera ( Shigella, Peptoclostridium, Peptostreptococcus, Streptococcus, Fusobacterium ). These microorganisms may partly result in the intestinal pathology of the infection. In summary, the discussion of the bacterial biodiversity in feces of CPV infected dogs provides further insights into the pathology of CPV disease and the targets of developing more effective treatment strategies. Highlights: First describe microbiome biodiversity in feces of CPV infected dogs to provide insights into the pathology of CPV. Obtained the bacterial diversity in feces of CPV infected dogs with the enrichment of five bacteria genera. Distinguished the significantly different bacterial communities in feces were affected by CPV infection.